Music Copyright Protection in the Digital Era: Legal Framework and Strategies for Enforcement - Hulman Panjaitan; Andrew Betlehn; Tomson Situmeang; Md Zubair Kasem Khan; Mahadi Hasan Miraz (Jurnal Hukum, 2024)
This research investigates the factors contributing to global music copyright infringement in the digital era, the legal framework established by Indonesian Law Number 28 of 2014 on Copyright, and strategies for strengthening protection. Using a doctrinal legal research approach, the study incorporates statutory and comparative legal analyses to assess the effectiveness of Indonesia’s copyright laws and proposed strategies. The findings indicate that digital piracy globally is primarily driven by technological advances, the ease of sharing pirated content, and inconsistent international copyright laws. These issues have resulted in significant financial losses for creators and the rise of new forms of piracy. In Indonesia, while Law Number 28 of 2014 provides robust protections for creators, including economic and moral rights, enforcement remains problematic due to low public awareness and the rapid pace of technological advancements. Key institutions, such as the Directorate General of Intellectual Property (Direktorat Jenderal Kekayaan Intelektual/DJKI) and Collective Management Institutions (Lembaga Manajemen Kolektif Nasional/LMKN), play a critical role in enforcement but need further support. The study recommends strengthening legal frameworks, international harmonization, and leveraging technological solutions such as blockchain to improve copyright enforcement in Indonesia and ensure fair compensation for artists.